Colligative and hydrodynamic properties of aqueous solutions of pectin from cornelian cherry and commercial apple pectin. (April 2019) - Pancerz, Michał; Ptaszek, Anna; Sofińska, Kamila; Barbasz, Jakub; Szlachcic, Paweł; Kucharek, Mateusz; Łukasiewicz, Marcin
Abstract: The analysis of literature revealed a certain lack of knowledge concerning Cornelian pectins, as well as a significant gap in the description of properties of apple pectin, and therefore the purpose of this study was to examine and compare the physicochemical properties of these compounds. Pectins from both sources were obtained using water extraction. Mass distribution was determined for each solution, physicochemical properties were measured using osmometry, DLS, and intrinsic viscosity; Atomic Force Microscopy (AFM) photos of the particles were recorded, together with their FT-IR spectra, and the ζ -potential was measured. Additionally both compounds were compared by X-ray diffraction revealing the amorphousness of the samples. Both polysaccharides exhibit polyion properties, but the results reveal considerable differences between them: industry-grade apple pectins have higher weight average molecular mass with strong dispersion, the Cornelian cherry pectins, unlike industry-grade apple ones, are poorly soluble in water. The Cornelian pectins' inability to aggregate is quite an unexpected behaviour, as is the presence of protein complexes, which are absent in industry-grade apple pectin. Graphical abstract: